Religious Character Education through Habituation at MTsN 2 Kediri: Pendidikan Karakter Beragama Melalui Pembiasaan di MTsN 2 Kediri - Rahmadin, Andika Nehru; astutik, anita puji (Indonesian Journal of Education Methods Development, 2025)
General background: Education plays a crucial role in shaping students’ values and behaviors, particularly in fostering religious character as a foundation for moral development. Specific background: At MTsN 2 Kediri City, habituation activities such as congregational Duha prayers, tahsinul Qur’an, and morning greetings are implemented to nurture students’ religiosity. Knowledge gap: While many studies emphasize character education broadly, limited research explores the systematic role of daily Islamic habituation activities in secondary-level madrasah. Aims: This study aims to describe how religious habituation activities contribute to strengthening students’ attitudes and behaviors aligned with Islamic teachings. Results: Using a qualitative case study with observations, interviews, and document review, the findings indicate that students developed habits of punctual congregational prayer, increased solemnity in worship, stronger ukhuwah Islamiyah, regular Qur’an recitation, love and understanding of tajwid, higher faith and piety, and improved social interactions through daily greetings. Novelty: This research highlights the integrated function of school-based habituation as a sustainable model for reinforcing Islamic character. Implications: The study suggests that systematic habituation can serve as a replicable strategy for Islamic schools in promoting lifelong religious values and social harmony. Highlights: Habituation strengthens students’ worship discipline and religiosity. Daily practices foster social harmony and Islamic brotherhood. Novelty lies in systematic integration of school-based religious activities. Keywords: Religious Character Education; Habituation; Islamic Values; Secondary Education; Social Harmony